1985
DOI: 10.3109/02841868509136063
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Irradiation Injury to Bone Tissue

Abstract: The dynamic changes after a single dose of 15, 25 or 40 Gy 60Co were followed in a titanium vital microscopic bone chamber which permitted observation of the same tissue compartment for over 2 years. The chamber consists of a hollow screw containing 2 glass rods 100 micron apart. The device was inserted into the cortex of the proximal tibial metaphysis of a rabbit. During a healing period of 4 to 6 weeks the space between the glass rods became filled with bone and vessels and in some cases fat. Once a steady s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Significantly reduced bone-regenerative capability and reduced implant osseointegration in irradiated dog and human alveolar bone have also been reported 23. The sensitivity to irradiation is higher for immature bone than for mature bone 24. Clinically, postoperative radiation therapy is commonly initiated 14 - 21 days after ablative surgery,10 at which time wound healing is not yet complete.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly reduced bone-regenerative capability and reduced implant osseointegration in irradiated dog and human alveolar bone have also been reported 23. The sensitivity to irradiation is higher for immature bone than for mature bone 24. Clinically, postoperative radiation therapy is commonly initiated 14 - 21 days after ablative surgery,10 at which time wound healing is not yet complete.…”
Section: Discussionmentioning
confidence: 99%
“…42 While effective in eradicating the damaged cells, previous reports confirm that irradiated defects have severely compromised bone healing due to the impairment in number and activity of endothelial and other tissue-forming cells. 43,44 Nussenbaum et al reported that in animals receiving radiation 2 weeks prior to surgery, inlay calvarial bone graft failed to heal at the wound margins by 4 weeks after surgery. 27 With a clinical eye toward healing irradiated bone defects resulting from head and neck cancer, we selected an irradiated bilateral calvarial defect for our animal model.…”
Section: Discussionmentioning
confidence: 99%
“…The corrosive impact of these radiationinduced side effects can be unrelenting and their complex management is rarely remedial. Radiation therapy changes the biologic environment of bone, resulting in a severe attenuation of cellularity and fibrosis [4,5], decreased vascular density, obliteration of small blood vessels, poor fracture and soft tissue healing [6][7][8][9], impaired growth [10], and the late devastating complication of osteoradionecrosis. The bone subjected to X-ray radiation therapy (XRT) demonstrates increased bone resorption, decreased osteogenesis, and reduced [11,12] mechanical strength [13] that predisposes the patients to the debilitating problem of late pathologic fractures with disastrous functional consequences [14].…”
Section: Introductionmentioning
confidence: 99%